Research on the ablation characteristics of combined lasers for glass fiber reinforced plastic composites - Xiao, Jing; Ren, Gang; Guo, Rongjun; Gan, Chunquan; Xu, Yongjun; Liu, Quanxi; Li, Shijie; Han, Dong; Lai, Gengxin (Frontiers in Physics, 2023)
Glass fiber reinforced plastic (GFRP) composites have been applied to the manufacture of missile shields and unmanned aerial vehicle (UAV) shells. It is of great significance to explore the ablation characteristics of different lasers for these composites. Currently, most existing studies on the ablation characteristics of lasers for GFRP composites are conducted under a single laser output mode, such as continuous wave (CW) laser or pulsed laser. However, the ablation characteristics of combined lasers for GFRP composites have not been clarified. Therefore, the ablation characteristics of single lasers (CW, millisecond (ms) pulsed, or nanosecond (ns) pulsed laser) and combined laser (CW/ms or CW/ns combined pulsed lasers) were investigated by experimental and simulation methods in this study. Additionally, the ablation mechanisms of GFRP under different laser irradiation conditions were compared and analyzed. The results demonstrated that the ablation rates of single lasers for GFRP composites were all within an order of magnitude of 10 μg/J, which was not significantly correlated with the light source system. The ablation efficiency of the single laser was determined by the incident laser energy. The CW laser was found to be the optimal light source for the ablation and destruction of GFRP composites. Nevertheless, there were some obstacles in the ablation process of CW lasers. Applying pulsed lasers during the irradiation of the CW laser may generate a synergistic effect. Under the conditions in this study, the CW/ns pulsed combined laser increased the ablation efficiency by 53.8%.